Handbook of East Asian new religious movements - Pokorny, Lukas, 1980- (Brill Handbooks on Contemporary Religion, 2018)
*This Handbook has won the ICAS Edited Volume Accolade 2019 . Brill warmly congratulates editors Lukas Pokorny and Franz Winter and their authors with this award.* A vibrant cauldron of new religious developments, East Asia (China/Taiwan, Korea, Japan, and Vietnam) presents a fascinating arena of related research for scholars across disciplines. Edited by Lukas Pokorny and Franz Winter, the Handbook of East Asian New Religious Movements provides the first comprehensive and reliable guide to explore the vast East Asian new religious panorama. Penned by leading scholars in the field, the assembled contributions render the Handbook an invaluable resource for those interested in the crucial new religious actors and trajectories of the region.